Sincronização do estro e da ovulação utilizando protocolos de curta duração durante a pré- estação reprodutiva em ovelhas Suffolk - Takada, Luciana; Bicudo, Sony Dimas [UNESP]; De Carvalho Rodrigues, Carlos Frederico; De Alencar Coelho, Lia; Perri, Silvia Helena Venturolli [UNESP] (Universidade Estadual de Maringa, 2009)
This study was carried out with the objective of examining the effect of the short-term estrus synchronization protocol. Ewes were divided in four groups: Control Group (MAP sponges for 12 days, and eCG at withdrawal); Groups I, II and III used the sponge for four days, and 100 μg of PGF was applied at withdrawal; and additionally, Group I (0.1 mg of Estradiol benzoate - EB, in the sponge placement, and in the withdrawn 400 UI of eCG and 50 μg of GnRH 48h later); Group II (35 mg of injectable progesterone and 0.1 mg of EB in the sponge placement, and 400 UI of eCG at withdrawal, and 50 μg of GnRH 48h after); Group III (35 mg of injectable progesterone and 0.2 mg of EB in the sponge placement, and 400 UI of eCG at withdrawal, and 50 ?g of GnRH 56h after). Exams were accomplished for ultrasound and determine the plasmatic concentrations of progesterone and observations of the beginning the estrus and the ovulation. The lack of eCG in Group I caused this protocol to be less efficacious in induction and synchronization of estrus and ovulation. The Control Group had a greater synchronization of estrus and ovulation.
Estrus and ovulation synchronization using short-term protocols during the previous reproductive season in Suffolk ewes
Keywords: ECG; Estradiol benzoate; GnRH; Progesterone; Ultrasound